Letter from Karl Vossler to Georg Bredig, January 1927 - Vossler, Karl (1927)
Karl Vossler (1872-1949), a German linguist and scholar of Romance languages at the University of Munich, thanks Georg Bredig (1868-1944) for sending his rector's speech "Denkmethoden der Chemie" (Methods of Thought in Chemistry).
Keywords: Vossler, Karl, 1872-1949; Bredig, Georg, 1868-1944; Speeches